2018
DOI: 10.3332/ecancer.2018.845
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of BMI with breast cancer subtype and tumour size

Abstract: BackgroundBreast cancer is a heterogeneous disease which is divided broadly into luminal, HER2 and basal type based on molecular profiling. Increased body mass index (BMI) has been associated with the risk of developing breast cancer but the association based on molecular subtype remains conflicting.MethodsThis was an observational study carried out over a period of 2 years. Nonmetastatic breast cancer patients were evaluated for the tumour subtype based on surrogate markers (ER, PR and HER2). The BMI of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The rare of our findings were PR and HER-2 inversely significantly correlated with BMI. The Babu (2018) and Kawai (2014) found similar findings; in both research pieces, there were variations in the correlation of BMI with the subtype of breast cancer 16,17 .…”
Section: Discussionmentioning
confidence: 69%
“…The rare of our findings were PR and HER-2 inversely significantly correlated with BMI. The Babu (2018) and Kawai (2014) found similar findings; in both research pieces, there were variations in the correlation of BMI with the subtype of breast cancer 16,17 .…”
Section: Discussionmentioning
confidence: 69%
“…12 Studies in Asia demonstrated that a higher BMI (≥25 kg/m 2 ) was associated with elevated risk of luminal and triple-negative subtypes, followed by triple-negative and lowest for HER2 at the time of diagnosis. 12,13 Specifically, BMI was significantly positively associated with increased risk of breast cancer for women with Luminal A tumour subtype. 14 Overweight and obesity may affect breast cancer by various mechanisms, including increasing oestrogen synthesis, generating insulin resistance, decreasing the synthesis of sex hormone-binding globulin (SHBG) and promoting systemic inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…This is a weakness inherent in the use of publicly available data that we readily acknowledge but is beyond the scope of this report. While our study did not address individual subtypes of TNBC, a previous epidemiologic study [ 49 ] has reported the correlation between BMI and breast cancer subtypes, suggesting that further investigation in this line of research may be warranted. However, such a study would require a much larger sample size, which was the rate limiting factor in this investigation.…”
Section: Discussionmentioning
confidence: 96%